A Corpus-Based Study of News Outlets’ Stances on Hezbollah in the 2024 Hezbollah-Israel Conflict - Sanjoyo, Emmanuel Christian Pratomo Putro; Ihsan, Muhammad Fazl; Sulthanulfalah, Mohammad Zaydan; Sujatna, Eva Tuckyta Sari (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2025)
This study examined news coverage from three news outlets namely, Al-Jazeera, Euronews, and the British Broadcasting Corporation, or BBC for short. The study investigated the political stance of which each news outlet holds on the topic of the 2024 Hezbollah-Israel conflict as seen in how they employ language patterns in their news coverage. The study used a mixed-method approach, using the corpus tool Sketch Engine to assist in the quantitative analysis and then using qualitative analysis on the gathered data to examine the political stance of each news outlet. The result of the study shows that Al-Jazeera and Euronews stand neutral while the BBC stands in favor of Hezbollah.